The Process of Learning Speech Skills Using The Direct Method ‎‎(Case Study in SMP IT Azkia Padang)‎ - Salsabila Aulia Zahra; Meliza Budiarti (Universitas Islam Negeri Imam bonjol Padang, 2023)
The purpose of this research is motivated by the advantages and ‎privileges of Arabic teachers, Arabic teachers always use direct ‎methods in the explanning learning material, and teachers also use ‎direct methodsin the Arabic language learning peocess at school, the ‎purpose of this research is to find out how to plan, implementation ‎and evalution of learning speaking skills using the direct method and ‎to find out the supporting factors and inhibiting factors of learning ‎Arabic at SMP IT Adzkia Padang. The type of research used is field ‎research with a descriptive qualitative approach. The results showed ‎that in process of teaching theskill of speaking by direct metod in the ‎SMP IT Adzkia Padang, the concluded in conducting learning ‎planning of teaching plan RPP that as been used, In the ‎implementation of teaching the Arabic language, the teacher gets ‎used to always using the Arabic language in explaining the subject, ‎and the Arabic language teacher cooperates with the English ‎language. In the evaluation of teaching the Arabic language, is is the ‎divided into the conciliatory evaluation, the knowledge evaluation, ‎then the skill evaluation. Giving the pratice of the dialogue material in ‎the from of oral, then giving the evaluation, then the skill evaluation ‎in the from of questions with exercises for vucabullary, and with ‎exercises for the dialogue written. Factors supporting Arabic learning ‎means having a BILLINGUAL (Arabic and English day) and Factors ‎hindering Arabic learning in the direct method way because of the ‎pipil’s heterogeneus condition‎